2022
DOI: 10.3390/ani12080997
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Modulation, Gut, and Omics Crosstalk in Ruminants

Abstract: Ruminant nutrition has significantly revolutionized a new and prodigious molecular approach in livestock sciences over the last decade. Wide-spectrum advances in DNA and RNA technologies and analysis have produced a wealth of data that have shifted the research threshold scheme to a more affluent level. Recently, the published literature has pointed out the nutrient roles in different cellular genomic alterations among different ruminant species, besides the interactions with other factors, such as age, type, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 189 publications
0
2
0
Order By: Relevance
“…The positive role of nutrition in improvement of milk production performance in ruminants has been extensively discussed in a recent study ( Abdelrahman et al, 2022 ). Consistently it is well-established that amino acids are taken up from the bloodstream into the mammary gland cells by specific transporters.…”
Section: Amino Acids Supplementation Regulates Milk Production Via Mt...mentioning
confidence: 99%
“…The positive role of nutrition in improvement of milk production performance in ruminants has been extensively discussed in a recent study ( Abdelrahman et al, 2022 ). Consistently it is well-established that amino acids are taken up from the bloodstream into the mammary gland cells by specific transporters.…”
Section: Amino Acids Supplementation Regulates Milk Production Via Mt...mentioning
confidence: 99%
“…Lam et al (2020) reported their study on Nellore beef cattle and they concluded that the optimization of RNA sequencing pipelines is the key factor to maximize power and accuracy to identify genetic variants including SNPs which may serve as genetic markers to select for feed efficiency, leading to economic benefits for beef production. Furthermore, Abdelrahman et al (2022) have summarized from published literature on the mechanism of premature feeding strategy in ruminant animals to elucidate the expression of targeted genes at the gastro intestinal tract related to the RFI as a precursor to energy intake. This finding suggests that there is a bright future of molecular approach to elucidate the genetic traits of feed efficiency in beef cattle for the sake of less feed consumption but resulting optimum production leading to economic benefits.…”
Section: The Importance Of Feed Efficiency Traits In Cattle Productionmentioning
confidence: 99%
“…Leptin, the product of the ob gene discovered in rodents ten years ago, may play a key role in the regulation of body energy homeostasis (appetite, energy expenditure, nutrient partitioning between tissues, and body composition), as well as hormone secretion by several endocrine glands, reproduction, immune and renal functions, hematopoiesis, angiogenesis, cell differentiation and proliferation [12]. The leptin gene was found to be expressed in ruminant AT, fetal tissues, mammary gland, abomasum and/or duodenum, and pituitary gland [13]. In rodents, humans, and ruminants, leptin may act not only as an endocrine signal in the brain and/or the very large number of peripheral tissues where leptin receptors are expressed, but also as an autocrine/paracrine signal within tissues where it is produced.…”
Section: Introductionmentioning
confidence: 99%